2021
DOI: 10.1111/cdev.13565
|View full text |Cite
|
Sign up to set email alerts
|

Corporal Punishment and Elevated Neural Response to Threat in Children

Abstract: Spanking remains common around the world, despite evidence linking corporal punishment to detrimental child outcomes. This study tested whether children (M age = 11.60) who were spanked (N = 40) exhibited altered neural function in response to stimuli that suggest the presence of an environmental threat compared to children who were not spanked (N = 107). Children who were spanked exhibited greater activation in multiple regions of the medial and lateral prefrontal cortex (PFC), including dorsal anterior cingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 60 publications
(90 reference statements)
1
36
0
3
Order By: Relevance
“…These effects are likely stronger when exposure happens in early childhood due to heightened neural plasticity (Berens & Nelson, 2019). Nascent evidence is consistent with these ideas, as children who were spanked in their first years of life exhibited greater activation in multiple circuits of the mPFC in response to stimuli that suggest the presence of an environmental threat relative to children who were not spanked (Cuartas et al, 2021). These findings also support the predictions from the social learning, social information, and attachment perspectives, by indicating that children who are spanked might devote greater attentional resources to processing threats in the environment (i.e., hypervigilance), have more difficulties engaging in effortful attempts to regulate emotional responses and regulating their behavior, and find it more challenging to resolve conflicts relative to children who are not spanked.…”
Section: Conceptual Links Between Spanking and Se Skillsmentioning
confidence: 76%
See 3 more Smart Citations
“…These effects are likely stronger when exposure happens in early childhood due to heightened neural plasticity (Berens & Nelson, 2019). Nascent evidence is consistent with these ideas, as children who were spanked in their first years of life exhibited greater activation in multiple circuits of the mPFC in response to stimuli that suggest the presence of an environmental threat relative to children who were not spanked (Cuartas et al, 2021). These findings also support the predictions from the social learning, social information, and attachment perspectives, by indicating that children who are spanked might devote greater attentional resources to processing threats in the environment (i.e., hypervigilance), have more difficulties engaging in effortful attempts to regulate emotional responses and regulating their behavior, and find it more challenging to resolve conflicts relative to children who are not spanked.…”
Section: Conceptual Links Between Spanking and Se Skillsmentioning
confidence: 76%
“…Social learning, social information processing, and attachment perspectives posit that spanking can undermine children's SE development, specifically their capacity to resolve social conflicts and regulate their emotions and behaviors. In addition, recent evidence showed that spanking is linked to atypical brain functioning in the medial frontal gyrus (MFG), dorsomedial prefrontal cortex (dPFC), bilateral frontal pole, and other regions of medial and lateral PFC (Cuartas et al, 2021). The MFG is often involved during effortful regulation of emotional responses and suppression of negative emotion (Goldin et al, 2008), whereas the dPFC and bilateral frontal pole tend to be engaged in social‐cognitive processes and social information processing (Buckner & DiNicola, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were drawn from a longitudinal study of children followed from age 3 and a caregiver, with the initial aim of studying the development of self-regulation in childhood ( 42 ). At age 11 to 12 years, between June 2017 and October 2018, before the pandemic, participants completed a baseline evaluation as part of a study examining mechanisms linking adverse childhood experiences with psychopathology ( 43 ). Participants were excluded from the study based on the following criteria: IQ < 80, active substance dependence, psychosis, presence of pervasive developmental disorders (e.g., autism), and psychotropic medication use.…”
Section: Methodsmentioning
confidence: 99%